Kelas Sosial Dan Perempuan Generasi Z di Surabaya Dalam Membuat Keputusan Setelah Lulus Sekolah Menengah Atas - Putranto, Teguh Dwi (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2018)
This paper describes how the social class determines the women generation Z in making decision after graduating from high school. From the results, it was obtained that women generation Z in Surabaya from upper middle and middle lower classes both have plans to continue their education to the university level after high school graduation. They both found that early-age marriege is not a goal when they have graduated from high school, because there are many things that should be prepared when they will reach the level of marriage. According to them the experience after graduating from high school such as working or pursuing their education at the university level is important for their lives in the future. Thus, it can be concluded that social class is so influential for the women generation Z in making decisions after graduating from high school. In addition, in the next six years the number of marriages of women generation Z will be decreased from the marriage of women generation Y. In the working world in the next six years will be fulfilled by many women generation Z Surabaya. Keywords: Social Class, Women, z generation